(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
This contribution investigates under which conditions consumers can identify a product’s country of origin when confronted with conflicting information on the product package. Our study draws on current literature on the country-of-origin effect and on foreign branding, a naming strategy designed to evoke associations of a favoured origin by means of the language or spelling cues included in the brand name. The study we conducted has two major objectives. The first one is to ascertain how much attention is paid to the country-of-origin at the point of sale. The second one is to clarify whether foreign branding effects can also be found in connection with the Croatian language. Therefore, an eye-tracking experiment with a follow-up questionnaire was conducted using a student sample. Results showed that attention can be distracted from the country of origin by positioning this element on the back label. Interestingly, findings also indicated that label design, price and shelf positioning influence the buying decision more than congruency of country of origin and brand name. It can further be concluded that incongruence between the country of origin and the language of the brand name seems to be less important for German and English branded olive oils. However, the results for Croatian branded olive oils were clearly better in a condition when those elements were congruent. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.